THE EFFECT OF RISK PERCEPTION AND TRUST ON CONSUMER SATISFACTION IN ONLINE SHOPPING IN PEKANBARU - Ibnu Abbas; Shahdanur; Shaefulloh; Nefrida (UPMI Management, 2022)
This research aims to determine and analyze the influence of risk perception and trust on consumer satisfaction in shopping online at JT Pekanbaru Sneaker. The population in this study were consumers who bought online, a sampling method with criteria or using the Roscoe technique to make it easier to get respondents so that the number of samples was as many as 100 people. The data collection technique uses questionnaires tested for validity and reliability. The data analysis techniques used are normality test, multiple linear regression, determination test, and hypothesis test. The results of this study show descriptively that most of the respondents who buy products online are in the excellent category. Based on the results of simultaneous testing, there is a positive and significant influence on consumer perception variables and trust in consumer satisfaction in shopping online. Meanwhile, in partial testing, the risk perception variable negatively affects consumer satisfaction in shopping online at JT Pekanbaru Sneakers. The trust variable significantly positively affects consumer satisfaction in shopping online at JT Pekanbaru Sneakers.